Biomonitoring of pesticides by pine needles - Chemical scoring, risk of exposure, levels and trends - Nuno Ratola (2014)
Vegetation is a useful matrix for the quantification of atmospheric pollutants such as semi-volatile organic compounds (SVOCs). In particular, pine needles stand out as effective biomonitors due to the excellent uptake properties of their waxy layer. Having previously validated an original and reliable method to analyse pesticides in pine needles, our work team set the objective of this study to determine the levels of 18 pesticides in Pinus pinea needles collected in 12 different sampling sites in Portugal. These compounds were selected among a total of 70 pesticides by previous chemical scoring, developed to assess their probability to occur in the atmosphere. The risk of exposure was evaluated by the binomial chemical score/frequency of occurrence in the analysed samples. Levels and trends of the chemical families and target of the pesticides were obtained regarding the type of land occupation of the selected sites, including the use of advanced statistics (principal component analysis, PCA). Finally, some correlations with several characteristics of the sampling sites (population, energy consumption, meteorology, etc.) were also investigated.